Assessment of the Dynamics and Condition of Post-Fire Forest Recovery in the Amankaragay Massif, Kostanay Region, Republic of Kazakhstan - Ozgeldinova, Zhanar; Zhanguzhina, Altyn; Mukayev, Zhandos; Berdenov, Zharas; Ulykpanova, Meruert (Journal of Multidisciplinary Applied Natural Science, 2025)
The study evaluates the dynamics and condition of post-fire forest recovery in the Amankaragay massif of the Kostanay region, Republic of Kazakhstan, which has been subjected to both natural and anthropogenic pyrogenic influences, resulting in structural transformations within the forest ecosystems and pyrogenic succession processes. The objective of this research is to assess natural forest regeneration after wildfires through an integrated approach, combining field studies and remote sensing data, and to analyze structural changes in forest landscapes due to fire disturbances. Three sample plots were selected for analysis: all affected by wildfires between 2004 and 2024, with assessments carried out using high- and medium-resolution satellite imagery. The methodology included the use of differenced normalized burn ratio (dNBR) analysis to assess fire severity, normalized difference vegetation index (NDVI) analysis to evaluate the intensity and dynamics of post-fire vegetation recovery, and geospatial analysis using ArcGIS 10.8. Additionally, supervised classification of satellite imagery and field surveys were conducted to validate remote sensing data. The results indicate significant structural changes in forest-forming species following fire disturbances, confirmed by both remote sensing and field data. As a result, the natural regeneration of forest ecosystems was evaluated, and significant findings were obtained. Fire intensity and type influence the rate of forest recovery. The dNBR and NDVI analyses confirm the effectiveness of remote sensing for monitoring post-fire forest recovery. Remote sensing data and field assessments enable not only the evaluation of the current forest condition but also predictions for its future development. This study underscores the effectiveness of remote sensing techniques in evaluating pyrogenic succession and contributes to a deeper understanding of natural forest regeneration processes in the region. The findings can inform the development of evidence-based strategies for forest ecosystem management and post-fire restoration efforts.